Exploring the Relationship Between Neighborhoods and Intimate Partner Violence - (:unkn) unknown (My University, 2016)
Background: Due to high prevalence rates and deleterious effects on individuals, families, and communities, intimate partner violence (IPV) is a significant public health problem. Because IPV occurs in the context of communities and neighborhoods, research must examine the broader environment in addition to individual-level factors to successfully facilitate behavior change. Stemming in part from the lack of theory, predictors of the relation between neighborhoods and intimate partner violence are under-identified, and a dearth of mediation studies exist that inductively build and deductively confirm theoretical frameworks. Methods: This dissertation contributes to gaps in the literature via a mixed methods study yielding three manuscripts, i.e., Chapters 2, 3, and 4. First, using a combined theoretical model to guide the analysis, an integrative review of the literature spanning 1995 to 2014 elucidates the field's understanding of predictors and potential mechanisms driving the relation between neighborhoods and IPV. Second, theory-informed neighborhood-level predictors of IPV were tested using hierarchical linear modeling. Third, using grounded theory and focus groups with 32 men in batterer intervention programs, processes by which neighborhoods influence men’s use of partner violence were explored. Results: Results from the first study indicate that macro-, exo-, and meso-level predictors and mediators in the proposed conceptual model have some empirical support; however, concepts at each ecological level have yet to be researched. In the second study concentrated disadvantage (i.e., neighborhood-level factor) and female-to-male partner violence (i.e., individual-level factor) were robust predictors of women’s IPV victimization. In the third study, three core categories -titled ACEs and Trauma, Structural Forces, and Systemic Forces - emerged from focused and axial coding, explaining how neighborhoods influenced men’s IPV perpetration. Theoretical coding illuminated how these core categories related to each other and their sequence of events. Implications: Considering the results of each study in context of one another suggests that a well-defined and integrative theoretical framework, that is inductively built and deductively refined, will enhance the field’s understanding of ecological effects on IPV via an expanded scope of predictors and potential underlying mechanisms. Furthermore, this work informs a comprehensive ecological approach to IPV aimed at prevention and intervention.
Keywords: Domestic Violence; Intimate Partner Violence; Mixed Methods; Neighborhoods